A Simulation Approach to Improve the VANETs Communication - Hassan, Hawraa abd Al_kadum; Zahraa Yaseen Hasan; Rusul H. Al Taie, (International Journal of Interactive Mobile Technologies (iJIM), 2022)
VANET ("vehicular ad hoc network") is a type of networks that consist of many vehicles acting as moving nodes. They are connected with other vehicles through an ad hoc wireless network so as to increase traffic security and provide relaxation to road users. Sending the messages to the final destination in VANETs is a challenging mission because of its relatively high mobility and dynamism. The clustering technique addresses such issues, as it gathers vehicles based upon several predefined metrics such us density, speed, and physical vehicles locations. Clustering in VANET is one of the controller techniques for dynamic form. In this paper, a new method is presented for clustering that suits the VANET environment with the purpose of improving the network cluster stability. This method takes a number of parameters into consideration, such as the coverage area and speed to make the cluster structure comparatively stable. In addition, and advance is obtained in tems of the cluster-head selections algorithm, and the data exchange is improved through clusters.